Exploring the effect of coloring mandalas on students’ math anxiety in business statistics courses - Ramos Salazar, Leslie (Business, Management and Economics Engineering, 2019)
Purpose – the purpose of this article is to review a quasi-experiment study examining whether business students’ math anxiety is reduced after participating in mandala coloring activities.Research methodology – the research methodology integrated quantitative methods including independent t-tests and ANOVAs in a non-random convenient sample of 106 undergraduate students in 2018 in Texas, United States.Findings – results from the one-way ANOVA and t-test analyses revealed that anxiety levels differed across groups, such that after coloring a pre-drawn mandala, math anxiety was significantly reduced in comparison to the control (doodling) group. Paired sample t tests also demonstrated that when comparing the anxiety levels at the baseline and post-treatment, math anxiety was reduced after performing both the pre-drawn and free-coloring mandala activities. Additionally, an independent sample t-test and a two-by-two factorial ANOVA demonstrated that males experienced a significant reduction in their math anxiety than the females did after performing the mandala coloring activity.Research limitations – the study used a convenient sample, self-reported items, and a math anxiety measurement. Also, the findings found short-term evidence of math anxiety.Practical implications – the findings of this study suggest that business statistics instructors who integrate a mandala coloring activity in anxiety-provoking undertakings may help to reduce their students’ math anxiety.Originality/Value – This study is the first to investigate mandala coloring to reduce math anxiety in business students. Unlike previous studies that focus on anxiety in general, this study examines the benefit of mandala coloring on students’ math anxiety.